Social responsibility in secondary markets - Marc Kaufmann; Malte Kornemann; Botond Kőszegi (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2025)
We study how secondary markets for durable goods interact with consumers' social-responsibility motives to mitigate environmentally harmful new production. On the positive side, secondary markets may allow responsible consumers to acquire used goods that would otherwise be discarded, reducing premature waste. On the negative side, secondary markets introduce two major harmful forces. First, the possibility of buying used goods and thereby causing less harm can raise the demand of responsible consumers, often increasing the production necessary to serve the market. Second, said demand can increase the price of used goods, encouraging purchases of new goods. These forces imply that if used goods have positive private consumption value, then secondary markets always erode the benefits of social responsibility. If, instead, used goods may have negative private value, then secondary markets can enhance or erode the benefits of social responsibility.
Keywords: D01; D11; D50; D62; D64; D91; 330; socially responsible consumers; climate change; externalities; secondary markets; durable goods; used goods